1996
DOI: 10.1128/jb.178.19.5850-5852.1996
|View full text |Cite
|
Sign up to set email alerts
|

The mitogen-activated protein kinase homolog HOG1 gene controls glycerol accumulation in the pathogenic fungus Candida albicans

Abstract: The Candida albicans HOG1 gene (HOG1 Ca ) was cloned by functional complementation of the osmosensitive phenotype associated with Saccharomyces cerevisiae hog1⌬ mutants. HOG1 Ca codes for a 377-amino-acid protein, 78% identical to S. cerevisiae Hog1p. A C. albicans hog1 null mutant was found to be sensitive to osmotic stress and failed to accumulate glycerol on high-osmolarity media.Fungi, like other microorganisms, are able to respond to changes in extracellular osmolarity, adjusting their intracellular compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
125
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 20 publications
10
125
2
Order By: Relevance
“…We present evidence that Pbs2 plays an important role in the response to oxidative and osmotic stress. Deletion of the PBS2 gene in C. albicans leads to the expected osmosensitive phenotype that has already been described for the hog1 mutant (San José et al, 1996), as also occurs with homologous routes in other organisms (Brewster et al, 1993;Millar et al, 1995;Shiozaki & Russell, 1995). The hierarchical relationship between Pbs2 and Hog1 regarding osmotic stress seems to be linear, as pbs2 and hog1 mutants displayed a similar osmosensitivity, independent of the osmolyte and the state of the medium (liquid or solid).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…We present evidence that Pbs2 plays an important role in the response to oxidative and osmotic stress. Deletion of the PBS2 gene in C. albicans leads to the expected osmosensitive phenotype that has already been described for the hog1 mutant (San José et al, 1996), as also occurs with homologous routes in other organisms (Brewster et al, 1993;Millar et al, 1995;Shiozaki & Russell, 1995). The hierarchical relationship between Pbs2 and Hog1 regarding osmotic stress seems to be linear, as pbs2 and hog1 mutants displayed a similar osmosensitivity, independent of the osmolyte and the state of the medium (liquid or solid).…”
Section: Discussionmentioning
confidence: 76%
“…Four MAP kinases have so far been identified in this organism: Mkc1, the homologue to the Slt2/Mpk1 MAP kinase from S. cerevisiae (NavarroGarcía et al, 1995), Cek1, homologue to Kss1 (Csank et al, 1998), Cek2, homologue to Fus3 (Chen et al, 2002) and Hog1, homologue to the Hog1 MAP kinase. Hog1 has been implicated in different functions in C. albicans, such as glycerol accumulation, morphological transitions, cellwall biogenesis and virulence (Alonso-Monge et al, 1999;San José et al, 1996). It has also been shown how this MAP kinase is phosphorylated when exposed to NaCl and hydrogen peroxide (Alonso-Monge et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. albicans HOG1 has been cloned in budding yeast and complements the lack of growth of a Saccharomyces cerevisiae hog1 mutant in a high-osmolarity medium. Likewise, the C. albicans hog1 mutant has been found to be unable to grow in the presence of high concentrations of extracellular solutes (NaCl, KCl, sorbitol) and also to accumulate internal glycerol in response to an osmotic challenge (San José et al, 1996). It was later found that Hog1p is implicated in morphogenesis, since hog1 mutants form filaments even under non-inducing conditions.…”
Section: Introductionmentioning
confidence: 99%